Extraction of His Bundle Pacing Lead: More Difficult than Coronary Sinus Lead Extraction: An Analysis of 3897 Lead Extraction Procedures Including 27 His and 253 Coronary Sinus Lead Removals - Paweł Stefańczyk; Wojciech Jacheć; Andrzej Kutarski; Paweł Dąbrowski; Andrzej Głowniak; Dorota Nowosielecka (Biomedicines, 2024)
Background: Experience with the transvenous extraction of leads used for His bundle pacing (HBP) is limited. Methods: Analysis of 3897 extractions including 27 HBP and 253 LVP (left ventricular pacing) leads. Results: The main reason for HBP lead extraction was lead failure (59.26%). The age of HBP and LVP leads (54.52 vs. 50.20 months) was comparable, whereas procedure difficulties were related to the LVP lead dwell time. The extraction of HBP leads > 40 months old was longer than the removal of younger leads (8.57 vs. 3.87 min), procedure difficulties occurred in 14.29%, and advanced tools were required in 28.57%. There were no major complications. The extraction time of dysfunctional or infected leads was similar in the HBP and LVP groups (log-rank p = 0.868) but shorter when compared to groups with other leads. Survival after the procedure did not differ between HBP and LVP groups but was shorter than in the remaining patients. Conclusions: 1. HBP is used in CRT-D systems for resynchronisation of the failing heart in 33.33%. 2. Extraction of HBP leads is most frequently performed for non-infectious indications (59.26%) and most often because of lead dysfunction (33.33%). 3. The extraction of “old” (>40 months) HBP leads is longer (8.57 vs. 3.87 min) and more difficult than the removal of “young” leads due to unexpected procedure difficulties (14.29%) and the use of second line/advanced tools (28.57%), but it does not entail the risk of major complications and procedure-related death and is comparable to those encountered in the extraction of LVP leads of a similar age. 4. Survival after lead extraction was comparable between HBP and LVP groups but shorter compared to patients who underwent the removal of other leads.